Az új közjogi irány : Az 1933 utáni németországi nemzetiszocialista alkotmányjogi változások visszhangja a korabeli magyarországi alkotmányjog-tudományban - Schweitzer, Gábor (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The National Socialist Party came to power in Germany in 1933. After that, Germany’s constitutional system was reformed based on the principles of National Socialism. The representatives of Hungarian constitutional law at the time showed an intense interest in the new totalitarian state systems, including Nazi Germany’s so-called new direction of public law. In the examined period, mainly the studies of István Egyed, professor of public law at the Technical University of Budapest, István Csekey, professor of public law at the University of Szeged, and Béla Török, clerk of the royal court, mainly presented the public law institutions of National Socialist Germany. Their objective went beyond the description and characterization of the constitutional solutions of totalitarian state systems, as they also sought an answer to the question of what the relationship is between the historically based Hungarian constitution and the public law solutions of totalitarian systems. The closer Hungary got to Nazi Germany in a political sense, the more pressing these questions arose. Is there an overlap between the concept of the historical constitution of Hungary and the new direction of public law? If there is, then why is there, and if not, would it be necessary to take over certain institutions? Is there a necessity to reform the historical constitution of Hungary under the influence of the new public law direction? If not, why not, and if so, how should the historical constitution of Hungary move in the direction of new public law solutions? The following paper would like to review mainly these questions.